Impact of vitamin D supplementation on disease activity and pain management in rheumatoid arthritis: a randomized double-blinded controlled study - Mjellma Rexhepi; Blana Krasniqi; Kreshnik Hoti; Armond Daci; Blerta Rexhepi-Kelmendi; Shaip Krasniqi (BMC Rheumatology)
Abstract Background Rheumatoid arthritis (RA) is a progressive autoimmune disease. During complex therapy, vitamin D supplementation could have an immunomodulatory effect and improve disease activity. Aim The aim of this study was to investigate the effects of vitamin D supplementation on laboratory parameters and the disease course among patients with RA. Methods This prospective, randomized, parallel-group, double-blind study with a follow-up period of 6 months aimed to investigate the effects of 4000 IU/day vitamin D on visual analogue scale (VAS) and disease activity score-28 (DAS-28) scores among RA patients treated at the Rheumatology Clinic of the University Clinical Centre of Kosova. The study included 100 RA patients (82 women and 18 men) who were divided into two groups: patients with vitamin D supplementation and patients without vitamin D supplementation. Results Our results revealed no significant differences in baseline clinical or laboratory parameters between the study groups. At the beginning of the study, to ensure homogeneity between the study groups, we compared inflammatory mediators between groups. We found no significant differences in the IL6 (H statistic of 1.79 for p.180), IL17 (H statistic of 0.015 for p.902), TNF (H statistic of 1.15 for p.284), ESR (H statistic of 0.085 for p.771) or CRP (H statistic of 1.45 for p.229) levels between the two groups. After six months of supplementation therapy, the vitamin D group showed significant differences in pain reduction (VAS score, U’=2245.5; P < 0.0001) and disease activity (DAS28 score, U’=2285.5; P < 0.0001). Conclusions Supplementation with 4000 IU/day of vitamin D can potentially improve disease activity and pain management among RA patients after six months. However, further research is needed with a focus on longer patient follow-up periods to determine the long-term benefits of vitamin D in RA patients. Trial registration ID NCT06716476, Date of Registration 04.12.2024.